2014
DOI: 10.4103/1319-2442.132186
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of carotid intimal-medial thickness with estimated glomerular filtration rate and cardiovascular risk factors in chronic kidney disease

Abstract: Carotid intimal-medial thickness (CIMT) predicts future vascular events in the general population. However, the correlation of traditional cardiovascular risk factors and stages of chronic kidney disease (CKD) with CIMT is not studied extensively. To determine the correlation of CIMT with traditional cardiovascular risk factors like age, body mass index (BMI), dyslipidemia and various stages of CKD patients, CIMT was measured by means of high-resolution B-mode ultrasonography in 70 CKD patients and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
4
11
0
1
Order By: Relevance
“…In a similar study of Chhajed et al, 8 higher prevalence of CKD among males (n=39 out of 70) with a mean age of 44.5 years (range 20-75 years) was reported. 9 In present study majority of patients had stage V CKD (67%), 21% had stage III and 14% had stage IV CKD. In the reports of Hinderliter et al nearly equal numbers had stage 3 (n = 86) and stage 4 (n = 88) CKD; 24 had stage 5 CKD.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In a similar study of Chhajed et al, 8 higher prevalence of CKD among males (n=39 out of 70) with a mean age of 44.5 years (range 20-75 years) was reported. 9 In present study majority of patients had stage V CKD (67%), 21% had stage III and 14% had stage IV CKD. In the reports of Hinderliter et al nearly equal numbers had stage 3 (n = 86) and stage 4 (n = 88) CKD; 24 had stage 5 CKD.…”
Section: Discussionsupporting
confidence: 48%
“…In agreement to present study findings Chhajed et al found that mean CIMT did not directly correlate with eGFR (r = -0130, P <0.283). 9 Preston et al 15 reported that patients with stage 3 to 4 CKD had increased CIMT compared with normotensive volunteers. Lu Xia Zhang et al, 16 in their study on stage 2-3 CKD patients (i.e., mild and moderate renal insufficiency), found significantly increased CIMT in these patients and concluded that arterial change might occur in the course of CKD earlier than previously believed.…”
Section: Discussionmentioning
confidence: 99%
“…Chhajed et al also obtained the same results where total cholesterol (r = 0.236, p≤0.018) and serum triglycerides (r = 0.387, p ≤0.001) correlated with cIMT thickening in CKD patients. [14][15][16][17] In this study no correlation was found between hormones parathyroid with carotid intima media thickness (cIMT) thickening (p = 0.180). Research Costa et al showed different results in which the correlation between parathyroid hormone and carotid intima medi thickening was obtained…”
Section: Discussionmentioning
confidence: 55%
“…На развитие структурных изменений ЛЖ и СА влияют также возраст, уровень АД и масса тела, что также подтверждается в нашем исследовании. При этом существует позитивная корреляция ТИМ ОСА со степенью развития коронарного атеросклероза, и поскольку этот фактор обладает прогностической значимостью в отношении развития клинических проявлений атеросклероза, он был предложен в качестве суррогатного маркера системного атеросклероза, в том числе при ХБП [20,21].…”
Section: Discussionunclassified